Best Answer

(2y-4)/(y+3)=(2-y-2)/(y+3) --> multiply both sides by (y+3)

2y-4=2-y-2 --> 2-2=0 (right hand side)

2y-4=-y --> add y to both sides

3y-4=0 --> add 4 to both sides

3y=4 --> divide both sides by 3

y=4/3

Q: Y2 - 4 over y plus 3 equals 2 - y - 2 over y plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2 +y2 = R2 =16 = radius 2 R = 4

x2+y2+4x+2y+3=0(x+2)2 + (Y+2.5)2 = 3This is the equation of circle with center at (-2,-2.5) with radius 3.5

Given: x2 + y2 - 10x + 4y + 4 = 0 First, we'll move our constants to the right: x2 + y2 - 10x + 4y = -4 Then group terms with the same variables together: x2 - 10x + y2 + 4y = -4 Then complete the squares: x2 - 10x + 25 + y2 + 4y + 4 = -4 + 25 + 4 (x - 5)2 + (y + 2)2 = 25 And there we have it. This is an equation for a circle whose center point is at (5, -2), with a radius of √25, which equals 5.

x2 + y2 = 144 = radius squared radius = sqrt (144) = 12 diameter = 2 x radius = 24

x = -1y = 33x2 - y2 = 3 (-1)2 - (3)2 = 3 (1) - 9 = -6

Related questions

y^2=-x^2-8x+6

(2-r)e-rr

a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z

X2+y2=25 (x-8)2+y2 =41

X2 or 2 times x?

If y=2 then that means x^2=9 and x= 3 or -3

If:xy = x2 + y2 + 2xyThen:x2 + xy + y2 = 0Do you want to solve it for x?x2 + xy + (y/2)2 = (y/2)2 - y2(x + y/2)2 = y2/4 - y2x + y/2 = ± √(-3y2/4)x = -y/2 ± y√(-3) / 2x = (-y ± yi√3) / 2

x2 +y2 = R2 =16 = radius 2 R = 4

There are several steps involved in how one can solve the derivative x plus y - 1 equals x2 plus y2. The final answer to this math problem is y'(x) = (1-2 x)/(2 y-1).

(2 pi) x sqrt(30)

The graph of that equation is a circle, centered at the origin, with radius = 2 .

X2+y2=25 (x-8)2+y2 =41